Note on the Banding of Adelie Penguin by the Summer Party of the 13th Japanese Antarctic Research Expedition (Reports of the Japanese Antarctic Research Expedition) - Masahiro AOYANAGI (National Institute of Polar Research, 1973)
1. Sixty three adult Adelie penguins were marked with an alminium flipper band by the writer (member of the biological group of the 13th Japanese Antarctic Research Expedition (JARE)) at two rookeries near Syowa Station 55 at Ongul Kalven Island (0011-0065), and 8 at Mame-zima Island (0071-0078). 2. Four banded penguins were recovered in January, 1972, by the writer and others. Two of them were recovered at Hinode rookery, twelve years after, they had been banded at Lutzow-Holm Bay by a member of the 4th JARE.